(untitled) (New York, 1998)
Covers clinically effective treatments for over twenty of the major mental, behavioral, and emotional diagnoses in the DSM-IV.The last two decades in social work have seen tremendous strides in field research, from the development of improved research designs to more accurate methods of problem measurement and outcome analysis. Drawing upon these significant advances, the two-volume Handbook of Empirical Social Work Practice brings together empirically validated interventions for many of the psychosocial problems most frequently encountered by social workers in their daily practice.
Keywords: Social case work,Psychiatric social work,Việc làm xã hội,Công tác xã hội